Effectiveness Of Supplementary Feeding (PMT) Against Height And Weight Gain Of Stunted Toddlers - Nurilah, Endah; Sri Futriani, Elfira (International Journal of Health and Pharmaceutical (IJHP), 2023)
WHO in 2020 stated that the prevalence of stunting under five worldwide was 22 percent or as many as 149.2 million. The prevalence of stunting in Indonesia (24.4%) is better than Myanmar (35%), but still higher than Vietnam (23%), Malaysia (17%), Thailand (16%) and Singapore (4%). The prevalence of stunting in West Java in 2021 is 24.5%, while in Bekasi Regency it is 21.3%. The impact of stunting is intelligence, impaired physical growth, high risk of diabetes, obesity, cancer, stroke, and low economic productivity. Knowing the effectiveness of giving supplementary food to the increase in height and weight of stunting toddlers. Quasi experimental with one group pretest-posttest design. The sample in this study were all 18 toddlers who experienced stunting at the Setiamekar Health Center in 2021 and 2022. The sampling technique used the total sampling technique. The average height of stunted toddlers before being given the Supplementary Feeding Biscuits was 74.06 kg and afterward was 89.51 kg. The average body weight of stunted toddlers before being given the Supplementary Feeding Biscuits was 9.05 kg and after that it was 13.22 kg. There is the effectiveness of giving supplementary food to the increase in height and weight of stunted toddlers with a p value of 0.000. There is the effectiveness of giving additional food to the increase in height and weight of stunted toddlers. It is hoped that health workers will provide counseling more often about the importance of providing balanced nutrition to toddlers to avoid stunting Reading List: 39 readings (2015-2021).